Depressão e ansiedade em idosos com e sem feridas crônicas - Correia, Analice de Souza Bandeira (2022)
Introduction: Brazil is experiencing an exponential growth of the elderly, which modifies its sociodemographic and epidemiological context of the elderly population, which requires scientific production to support the acquisition of specific skills and abilities to promote a care practice focused on holistic and specialized care for this population. especially regarding comprehensive care for chronic diseases and mental disorders. Objective: To verify the occurrence of depression and anxiety in elderly people with and without chronic wounds and to establish their relationship with sociodemographic and clinical aspects. Method: Descriptive study, with a quantitative approach, carried out at the Geriatrics outpatient clinic and the Skin Commission of a University Hospital located in the capital of Paraíba. The study population consisted of two groups, elderly without wounds and elderly with chronic wounds, 140 individuals were included in the sample. A structured form was applied containing sociodemographic and clinical variables, brief history of mental health and wound characteristics, in addition to the Geriatric Anxiety Inventory (GAI) and the Geriatric Depression Scale (GDS-15). The analysis of the data of article one, the descriptive analysis of the variables was carried out, through the absolute and relative frequency and inferential analysis of the data, through the application of Pearson's Chi-square, Fisher's Exact, Spearman's Correlation and Model of Multiple Logistic Regression. For article two, the analysis was descriptive using absolute and relative frequency and measures of central tendency and dispersion (mean, standard deviation, minimum and maximum). In both articles SPSS software version 26.0 was used. Results: They are arranged in two original articles, the characterization of the sample occurred in a similar way in both manuscripts, of which the majority of the elderly presented a sociodemographic profile: female, Catholic, brown, with incomplete elementary education, retired, who earn between one and two minimum wages and live with their families. There was a prevalence of cardiovascular and metabolic diseases. Regarding the brief history of Mental Health, most of the elderly people reported not being assisted by a psychiatrist or psychologist, they do not use psychotropic drugs, nor do they have any diagnosis of mental disorder. In article one, the GDS-15 and GAI scores revealed that the studied sample has a higher prevalence of depressive symptoms than anxiety, in addition, depressive symptoms were more prevalent among the elderly with chronic wounds. It was not possible to establish a statistically significant relationship between the GDS-15 and GAI scores and the sociodemographic and clinical aspects. In article two, for both groups of elderly there was a higher prevalence of Depression than Anxiety, although the scores were higher among the elderly without wounds. Conclusion: It was possible to verify an occurrence of depressive symptoms with a higher prevalence in relation to Anxiety among the studied sample, mainly among the elderly with chronic wounds, although this variable is not relevant to differentiate the results between the two groups of elderly people, perhaps, due to the limitation of the study residing in the fragility of the sample, influenced by the COVID-19 Pandemic and the limited turnover of patients in the Skin Commission. This study has significant implications for clinical practice, teaching and research, in addition, it presents results that can be used in the routine of outpatient clinics that serve the elderly. Thus, supporting reflections on care practice.